2017
DOI: 10.29333/iejme/621
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mediating Role of Learning Strategies (Cognitive and Metacognitive) between Emotional Intelligence and Academic Performance among Students of Smart and Ordinary School

Abstract: Education system is efficient and successful when the academic achievement of students in different periods shows highest and lowest numbers. Smart schools are an environment that has the potential necessary to accomplish this goal. However, academic performance is affected by many variables. The aim of this study was investigating the mediating role of learning strategies (cognitive and metacognitive) between emotional intelligence and academic performance among students of smart and ordinary school. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…This shows that only certain components in classroom climate are influenced by knowledge of cognition. Thus, the findings of the current study regarding student cohesiveness contradict the result of Sadipour et al (2017) andWentzel et al (2018). More specifically, student with positive emotion tends to participate and interact with other students in the classroom, affect the use of learning strategies such as metacognitive strategies and lead to the improvement of students' academic performance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This shows that only certain components in classroom climate are influenced by knowledge of cognition. Thus, the findings of the current study regarding student cohesiveness contradict the result of Sadipour et al (2017) andWentzel et al (2018). More specifically, student with positive emotion tends to participate and interact with other students in the classroom, affect the use of learning strategies such as metacognitive strategies and lead to the improvement of students' academic performance.…”
Section: Discussioncontrasting
confidence: 99%
“…Literature has shown that knowledge of cognition serves as a mediator in many different contexts related to learning outcomes, including students' academic achievement. Sadipour et al (2017) study on the mediation effect of metacognitive learning strategies found that metacognitive learning strategies mediate the relationship between emotional intelligence which is connected to the students' positive emotion and students' academic performance. Based on structural equation modelling (SEM) results, it was concluded that the psychological aspects have affected students' approach to learning strategies such as metacognitive and this leads to effective learning and thus improve students' academic performance.…”
Section: Mediation Effect Of Knowledge Of Cognition In Classroom Clim...mentioning
confidence: 99%
“…The findings implied that academic motivation, emotional expression, and conscientiousness were the determinants of undergraduate students' academic achievement. This finding coincided with previous findings by De Feyter et al (2012);Hazrati-Viari et al (2012); Mammadov et al (2021); Mega et al (2014); Nazim and Ahmad (2013); Ning and Downing (2012);Önder et al (2014); Sadipour et al (2017); Tam et al (2021); Trigueros et al (2019);Tripathi et al (2018); Xu and Wu (2017) found that academic motivation were the significant factors of students' academic achievement.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research by Sadipour et al (2017); Khan (2019) discovered that EI significantly impacted student accomplishment. Aghamohammadi and Asgari (2016); Iqbal et al (2021); Marjanović et al (2021); Okwuduba et al (2019) found that some dimensions of emotional intelligence contributed to student achievement.…”
Section: Emotional Intelligence and Academic Achievementmentioning
confidence: 95%
See 1 more Smart Citation